Reproducible Functional Tests for Multi-scale Network Services - Nuriddinov, Askhat; Tavernier, Wouter; Colle, Didier; Pickavet, Mario; Peuster, Manuel; Schneider, Stefan Balthasar (IEEE Conference on Network Function Virtualization and Software Defined Networks (NFV-SDN))

FOP4: Function Offloading Prototyping in Heterogeneous and Programmable Network Scenarios - Moro, Daniele; Peuster, Manuel; Karl, Holger; Capone, Antonio (IEEE Conference on Network Function Virtualization and Software Defined Networks (NFV-SDN))
Offloading packet processing tasks to programmable switches and/or to programmable network interfaces, so called “SmartNICs”, is one of the key concepts to prepare softwarized networks for the high traffic demands of the future. However, implementing network functions that make use of those offload- ing technologies is still challenging and usually requires the availability of specialized hardware. It becomes even harder if heterogeneous services, making use of different offloading and network virtualization technologies, should be developed. In this paper, we introduce FOP4 (Function Offloading Pro- totyping with P4), a novel prototyping platform that allows to prototype heterogeneous software network scenarios, including container-based, P4-switch-based, and SmartNIC-based network functions. The presented work substantially extends our existing Containernet platform with the means to prototype offloading scenarios. Besides presenting the platform’s system design, we evaluate its scalability and show that it can run scenarios with more than 64 P4 switch or SmartNIC nodes on a single laptop. Finally, we presented a case study in which we use the presented platform to prototype an extended in-band network telemetry use case.

Demonstrating FOP4: A Flexible Platform to Prototype NFV Offloading Scenarios - Moro, Daniele; Peuster, Manuel; Karl, Holger; Capone, Antonio (IEEE Conference on Network Function Virtualization and Software Defined Networks (NFV-SDN))
Emulation platforms supporting Virtual Network Functions (VNFs) allow developers to rapidly prototype network services. None of the available platforms, however, supports experimenting with programmable data planes to enable VNF offloading. In this demonstration, we show FOP4, a flexible platform that provides support for Docker-based VNFs, and VNF offloading, by means of P4-enabled switches. The platform provides interfaces to program the P4 devices and to deploy network functions. We demonstrate FOP4 with two complex example scenarios, demonstrating how developers can exploit data plane programmability to implement network functions.

Putting NFV into Reality: Physical Smart Manufacturing Testbed - Müller, Marcel; Behnke, Daniel; Bök, Patrick-Benjamin; Schneider, Stefan Balthasar; Peuster, Manuel; Karl, Holger (IEEE Conference on Network Function Virtualization and Software Defined Networks (NFV-SDN))

NFV-driven intrusion detection for smart manufacturing - Behnke, Daniel; Müller, Marcel; Bök, Patrick-Benjamin; Schneider, Stefan Balthasar; Peuster, Manuel; Karl, Holger (IEEE Conference on Network Function Virtualization and Software Defined Networks (NFV-SDN))

Towards Analyzing High Street Customer Trajectories - A Data-Driven Case Study - Berendes, Carsten Ingo (Business Information Systems Workshops)

New Quick And Easy Publication - Will be edited by LibreCat team - Jochen Baumeister (Quick And Easy Journal Title)

Negative Emotion and Joint-Stiffness Regulation Strategies After Anterior Cruciate Ligament Injury. - An, YW; Lobacz, AD; Baumeister, Jochen; Rose, WC; Higginson, JS; Rosen, J; Swanik, CB (J Athl Train)

Virtual reality interventions for balance prevention and rehabilitation after musculoskeletal lower limb impairments in young up to middle-aged adults: A comprehensive review on used technology, balance outcome measures and observed effects. - Vogt, Sarah; Skjæret-Maroni, N; Neuhaus, D; Baumeister, Jochen (Int J Med Inform)

Optimization of Application-specific L1 Cache Translation Functions of the LEON3 Processor - Ho, Nam; Kaufmann, Paul; Platzner, Marco (World Congress on Nature and Biologically Inspired Computing (NaBIC))

Phase Coupling of Bilateral Motor Areas Decreases from Bipedal to Single Leg Stance - Lehmann, Tim; Büchel, Daniel; Cockcroft, John; Louw, Quinette; Baumeister, Jochen

Principles of Motor Learning to Support Neuroplasticity After ACL Injury: Implications for Optimizing Performance and Reducing Risk of Second ACL Injury. - Gokeler, Alli; Neuhaus, D; Benjaminse, A; Grooms, DR; Baumeister, Jochen (Sports Med)

Neuroplastic changes in anterior cruciate ligament reconstruction patients from neuromechanical decoupling. - An, YW; DiTrani Lobacz, A; Lehmann, T; Baumeister, Jochen; Rose, WC; Higginson, JS; Rosen, J; Swanik, CB (Scand J Med Sci Sports)

Test-retest reliability and discriminative ability of forward, medial and rotational single-leg hop tests. - Dingenen, B; Truijen, J; Bellemans, J; Gokeler, A (Knee)

Model-Driven Engineering of Self-Adaptive User Interfaces - Yigitbas, Enes

OpenCL Implementation of Cannon's Matrix Multiplication Algorithm on Intel Stratix 10 FPGAs - Gorlani, Paolo; Kenter, Tobias; Plessl, Christian (Proceedings of the International Conference on Field-Programmable Technology (FPT))
Stratix 10 FPGA cards have a good potential for the acceleration of HPC workloads since the Stratix 10 product line introduces devices with a large number of DSP and memory blocks. The high level synthesis of OpenCL codes can play a fundamental role for FPGAs in HPC, because it allows to implement different designs with lower development effort compared to hand optimized HDL. However, Stratix 10 cards are still hard to fully exploit using the Intel FPGA SDK for OpenCL. The implementation of designs with thousands of concurrent arithmetic operations often suffers from place and route problems that limit the maximum frequency or entirely prevent a successful synthesis. In order to overcome these issues for the implementation of the matrix multiplication, we formulate Cannon's matrix multiplication algorithm with regard to its efficient synthesis within the FPGA logic. We obtain a two-level block algorithm, where the lower level sub-matrices are multiplied using our Cannon's algorithm implementation. Following this design approach with multiple compute units, we are able to get maximum frequencies close to and above 300 MHz with high utilization of DSP and memory blocks. This allows for performance results above 1 TeraFLOPS.

P2.9 Comparison of deep feature extraction techniques for varying-length time series from an industrial piercing press - Thiel, Christian; Steidl, Carolin; Henning, Bernd (20. GMA/ITG-Fachtagung. Sensoren und Messsysteme 2019)
The continuous refinement of sensor technologies enables the manufacturing industry to capture increasing amounts of data during the production process. As processes take time to complete, sensors register large amounts of time-series-like data for each product. In order to make this data usable, a feature extraction is mandatory. In this work, we discuss and evaluate different network architectures, input pre-processing and cost functions regarding, among other aspects, their suitability for time series of different lengths.
Keywords: Dynamic Time Warping; Feature Extraction; Masking; Neural Networks

Zur Gestaltung von Feedbackprozeduren zum Erlernen der postoperativen Teilbelastung beim Gehen mit Unterarmgehstützen im Kontext der Bewegungsautomatisierung - Krause, Daniel; Paschen, Linda; Vogt, Sarah (B&G Bewegungstherapie und Gesundheitssport)
Zusammenfassung Training mit ergänzendem verzögertem Feedback zeigt sich zum Erlernen einer postoperativen Teilbelastung beim Gehen an Unterarmgehstützen effektiv. Insbesondere die Verwendung von Bandbreitenfeedback hat sich bei anderen Bewegungsaufgaben im Hinblick auf die Ausführungspräzision, -konstanz und -automatizität als vorteilhaft erwiesen. In einer Studie mit 31 jungen gesunden Erwachsenen untersuchten wir diese Parameter im Rahmen eines Feedbacktrainings während einer Teilbelastungsaufgabe und verglichen dabei eine Bandbreitenmethode mit einem 100 %-Feedback und einer Kontrollbedingung. Die in anderen Studien aufgezeigten Vorteile des Bandbreitenfeedbacks konnten in diesem Kontext für keinen der 3 Zielparameter gezeigt werden. Darüber hinaus ergeben sich aus den Daten 2 wichtige Hinweise für die rehabilitative Praxis: Zum einen konnten mit nur wenigen feedbackgestützten Übungsversuchen deutliche und zudem relativ behaltensstabile Reduktionen der Teilbelastung erreicht werden, zum anderen zeigte sich, dass das Teilbelastungsgehen einen hohen kognitiven Aufwand erfordert, der sich auch nach 2 umfangreichen Übungssitzungen nicht verringert und dazu führt, dass die Einhaltung der Teilbelastung bei Aufmerksamkeitsablenkung im Alltag beeinträchtigt sein könnte.

Value Co-Creation Patterns in Multi-Actor Service Interactions: A Framework for Collaborative Consumption Platforms - Purrmann, Maren; Wünderlich, Nancy (Proceedings of the 2019 Frontiers in Service Conference)

Program Comprehension: Identifying Learning Trajectories for Novice Programmers - Izu, Cruz; Schulte, Carsten; Aggarwal, Ashish; I. Cutts, Quintin; Duran, Rodrigo; Gutica, Mirela; Heinemann, Birte; Kraemer, Eileen; Lonati, Violetta; Mirolo, Claudio; Weeda, Renske (Proceedings of the 2019 (ACM) Conference on Innovation and Technology in Computer Science Education, Aberdeen, Scotland, UK, July 15-17, 2019)